ANALISIS PERILAKU POLITIK GENERASI MILENIAL DAN Z INDONESIA DALAM VIRTUAL SPHERE - Wahyudi, Wahyudi; Loilatu, Mohammad Jafar (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2023)
Quantitatively, penetration of Indonesian internet and social media users has increased sharply in the last two years, because it is ranked third in the world. Social media has become a new form of public sphere which is then called the virtual sphere. Social media as a virtual sphere is used by the millennial and Z generations to respond, criticize and build public opinion related to political issues in Indonesia. This research aims to determine the development of political behavior of the Indonesian millennial and Z generation in the virtual sphere. The theoretical basis used is Jurgen Habermas's public sphere theory and Papacharissi's Virtual Sphere theory. The results of the analysis show that the political behavior of the millennial and Z generations in the virtual sphere is influenced by their respective backgrounds. The behavior of the Indonesian millennial and Z generations tends to be impolite. The younger generation tends to carry out cyberbullying, hate speech, hoaxes and character assassination against parties who have different political views.